Consumption-Based Estimates of Carbon Footprint and Its Global Warming Solution: Input to Awareness Campaign - Isiderio, Eries D.; Dacles, Ginalyn G.; Yap, Ma. Consuelo Y.; Solano, Ma. Lida A.; Obidos, Ivy Dell (Future Science / FSH-PH Publications, 2024)
Understanding the consequences of everyday consumption, and learning how to reduce the size of collective carbon footprint, are vital to reducing CO2 emissions and slowing down human caused climate change. A carbon footprint is a measure of the amount of greenhouse gases (CO2, methane, nitrous oxide) measured in units of carbon dioxide, produced by human activities. This study aimed to quantify the carbon footprint and awareness in solving global warming of teachers and students in the College of Education based on consumptions’ estimates categorized into food consumption, energy usage and household activities. The measurement of Carbon footprint of student-respondents was determined as a whole and by specialization. A number of 296 student-respondents specializing in Filipino, English, Science, TLEd and PEd had a comparable carbon dioxide emission and contributed almost the same percentage in the total carbon footprint considering the different activities they engaged in. While the 35 teacher-respondents had greatest carbon footprint in their type and choices of food consumed. These data were gathered using a survey questionnaire through google form containing different activities with corresponding points associated to greenhouse gases emission. The total emission was computed using this formula: Total Emission (tCO2e) = Activity Data Points in (lbs.) X Emission Factor (tCO2) X Global Warming Potential (e). The result implies that the average carbon footprint of each respondent ranges from 2.04 to 2.55 tCO2e which is below the global average of 4 tCO2e per person. The “average” level of awareness implies that the respondents need to change their lifestyles to cut down carbon footprint but increase knowledge in solving global warming using the developed information and awareness campaign recorded video clip.